Immunosuppression after kidney transplantation - Kihm, Lars Philipp; Zeier, Martin; Morath, Christian (Minerva urologica e nefrologica, 2011)
Today kidney transplantation features excellent short-term outcomes with decreasing acute rejection episodes. In contrast, improvement of long-term allograft survival is much less impressive over the last decades. Thus, the goal of current immunosuppressive therapies is keeping the balance between the reduction of acute rejection episodes and organ specific and systemic side effects. With the development of a broad armamentarium of new immunosuppressive agents with different mechanisms of action, the minimization or avoidance of corticosteroids and calcineurin inhibitors became feasible.